Type specimens of Elasmobranchii in the Museu de Zoologia da Universidade de São Paulo (MZUSP) - Lima, Arthur De; Loboda, Thiago Silva; Gianeti, Michel Donato; Silva, João Paulo Capretz Batista Da; Pinna, Mario De (Zootaxa, 2023)
The type specimens of the subclass Elasmobranchii deposited in the Museu de Zoologia da Universidade de São Paulo are compiled in an annotated list, including updated measurements, verified collection data and recent photographs of holotypes and selected paratypes. Relevant information on the preservation condition of the specimens and their current taxonomic status are also provided. The collection holds a total of 135 lots of type specimens of elasmobranchs, three holotypes and seven paratypes in the division Selachii plus 16 holotypes, one neotype, and 108 paratypes in the division Batoidea (total specimen count: 137). Four paratypes were not located and one was donated to another institution, and publication mistakes in catalog numbers and locality assignments are corrected. The vast majority of specimens belong to the neotropical freshwater stingrays (subfamily Potamotrygoninae). The present catalogue intends to facilitate taxonomic research by providing access to updated information on type specimens of mostly large-sized taxa, which are notoriously difficult or impossible to examine outside of their home institution.